Virulence capacity of different Aspergillus species from invasive pulmonary aspergillosis - Chen, Biao; Qian, Guocheng; Yang, Zhiya; Zhang, Ning; Jiang, Yufeng; Li, Dongmei; Li, Renzhe; Shi, Dongmei (Frontiers in Immunology, 2023)
The opportunistic filamentous fungus Aspergillus causes invasive pulmonary aspergillosis (IPA) that often turns into a fatal infection in immunocompromised hosts. However, the virulence capacity of different Aspergillus species and host inflammation induced by different species in IPA are not well understood. In the present study, host inflammation, antimicrobial susceptibilities and virulence were compared among clinical Aspergillus strains isolated from IPA patients. A total of 46 strains were isolated from 45 patients with the invasive infection, of which 35 patients were diagnosed as IPA. Aspergillus flavus was the dominant etiological agent appearing in 25 cases (54.3%). We found that the CRP level and leukocyte counts (elevated neutrophilic granulocytes and monocytes, and reduced lymphocytes) were significantly different in IPA patients when compared with healthy individuals (P < 0.05). Antifungal susceptibilities of these Aspergillus isolates from IPA showed that 91%，31%，14%，and 14% were resistant to Fluconazole, Micafungin, Amphotericin B and Terbinafine, respectively. The survival rate of larvae infected by A. flavus was lower than larvae infected by A. niger or A. fumigatus (P < 0.05). Given the prevalence of A. flavus in our local clinical settings, we may face greater challenges when treating IPA patients.